Analisis Pengelolaan Keuangan Pada Brand Teh Poci Di Wilayah Kecamatan Tanjungsari Kabupaten Sumedang - Fauzi, Rizka; Gunawan, Gunawan (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses financial management at the Teh Poci franchise in Tanjungsari District, Sumedang Regency which is focused on four main elements, namely planning, recording, reporting, and control. The purpose of this study was to determine how the implementation of financial management in the Teh Poci Franchise Business in Tanjungsari District. This type of research uses a qualitative approach which is used through interviews and direct observation of business actors. The informants in this study were 5 (five) teapot tea franchisees in Tanjungsari District, Sumedang Regency. The results showed that most business actors faced obstacles in systematic financial management due to a lack of understanding of basic accounting, limited human resources, and low awareness of the importance of accurate financial records. As a result, many business owners have difficulty separating personal and business finances, which results in inaccurate financial management and strategic decision-making. Of the four elements of financial management, only two are commonly applied, while reporting and controlling are still rarely done.